Impact of maternal body mass index and gestational weight gain on pregnancy complications: an individual participant data meta‐analysis of European, North American and Australian cohorts. (20th March 2019) - Santos, S; Voerman, E; Amiano, P; Barros, H; Beilin, LJ; Bergström, A; Charles, M‐A; Chatzi, L; Chevrier, C; Chrousos, GP; Corpeleijn, E; Costa, O; et al.
Abstract : Objective: To assess the separate and combined associations of maternal pre‐pregnancy body mass index (BMI) and gestational weight gain with the risks of pregnancy complications and their population impact. Design: Individual participant data meta‐analysis of 39 cohorts. Setting: Europe, North America, and Oceania. Population: 265 270 births. Methods: Information on maternal pre‐pregnancy BMI, gestational weight gain, and pregnancy complications was obtained. Multilevel binary logistic regression models were used. Main outcome measures: Gestational hypertension, pre‐eclampsia, gestational diabetes, preterm birth, small and large for gestational age at birth. Results: Higher maternal pre‐pregnancy BMI and gestational weight gain were, across their full ranges, associated with higher risks of gestational hypertensive disorders, gestational diabetes, and large for gestational age at birth. Preterm birth risk was higher at lower and higher BMI and weight gain. Compared with normal weight mothers with medium gestational weight gain, obese mothers with high gestational weight gain had the highest risk of any pregnancy complication (odds ratio 2.51, 95% CI 2.31– 2.74). We estimated that 23.9% of any pregnancy complication was attributable to maternal overweight/obesity and 31.6% of large for gestational age infants was attributable to excessive gestational weight gain. Conclusions: Maternal pre‐pregnancy BMI and gestational weight gain are, across their full ranges, associated with risks of pregnancy complications. Obese mothers with high gestational weight gain are at the highest risk of pregnancy complications. Promoting a healthy pre‐pregnancy BMI and gestational weight gain may reduce the burden of pregnancy complications and ultimately the risk of maternal and neonatal morbidity. Tweetable abstract: Promoting a healthy body mass index and gestational weight gain might reduce the population burden of pregnancy complications. Tweetable abstract: Promoting a healthy body mass index and gestational weight gain might reduce the population burden of pregnancy complications.